Tasikmalaya Oktober Festival sebagai Pembuktian Destinasi Wisata Industri Kreatif dalam Memasarkan Produk Unggulan ke Mancanegara - Yani Sri Mulyani (Khasanah Ilmu - Jurnal Pariwisata Dan Budaya, 2018)
Abstract - Tasikmalaya October Festival is an annual event held by the government of the city of Tasikmalaya in commemoration of the anniversary of the city of Tasikmalaya every October. The implementation of TOF itself is a joint event of major events which become an annual agenda in the City of Tasikmalaya. One of them is Tasik Halal Culinary Festival, Tasik Investment Expo & Conference (TIEC), Tasikmalaya Culture & Craft Festival, and Tasikmalaya Creative Festival (TCF). The activity was enlivened by the appearance of several special Tasikmalaya arts as well as the video profile screening of the City of Tasikmalaya which received a warm welcome from the ministry and all invitations present at the event. The Tasikmalaya city also became the pillar of industrial development for the regions in the eastern Priangan region. all of these potentials can be maximally utilized, especially in boosting the regional economy, there needs to be simultaneous and targeted promotion As is known, the City of Tasikmalaya has at least 4,500 small and medium scale creative industrial units, the creative industries in Tasikmalaya are not only embroidery, but also now batik is on the rise. The city of Tasikmalaya with all its capital and creative industry potential is indeed deserved to be encouraged so that it becomes the most advanced tourism city in East Priangan. The research method used is descriptive qualitative, analyzing only to the descriptive level, systematically analyzing and presenting facts so that it can be easier to be understood and concluded, as well as documentation and literature study, the results of the above research were concluded with the holding of the Tasik Oktober Festival to boost tourists to visit Tasikmalaya and had a positive impact on Tasikmalaya's economic activities. Keywords: Tasik October Festival (TOF), creative industry, Abstrak - Perhelatan Tasikmalaya October Festival merupakan event tahunan yang diselengarakan oleh pemerintah kota Tasikmalaya dalam rangka memperingati hari jadi kota Tasikmalaya setiap bulan oktober. Pelaksanaan TOF sendiri merupakan ajang gabungan event-event besar yang menjadi agenda tahunan di Kota Tasikmalaya. Salah satunya adalah Tasik Halal Culinary Festival, Tasik Invesment Expo & Conference (TIEC), Tasikmalaya Culture & Craft Festival, serta Tasikmalaya Creative Festival (TCF). Kegiatan itu dimeriahkan oleh tampilan beberapa kesenian khas Tasikmalaya serta pemutaran video profil Kota Tasikmalaya yang mendapat sambutan hangat dari pihak kementerian dan seluruh undangan yang hadir dalam kegiatan tersebut.Kota Tasikmalaya pun menjadi penopang pembangunan industri bagi daerah-daerah yang berada di wilayah Priangan timur.Agar seluruh potensi tersebut bisa dimanfaatkan secara maksimal, terutama dalam mendongkrak perekonomian daerah, maka perlu ada promosi yang simultan dan tepat sasaran Seperti diketahui, Kota Tasikmalaya memiliki sedikitnya 4.500 unit industri kreatif berskala kecil menengah dan mikro,industri kreatif di Kota Tasikmalaya tidak hanya bordir, tapi juga batik yangsekarang tengah naik daun. Kota Tasikmalaya dengan segala modal dan potensi industri kreatifnya, memang pantas untuk terus didorong sehingga menjadi kota pariwisata termaju di Priangan Timur.. Metode penelitian yang digunakan yaitu deskriptif kualitatif,menganalisis hanya sampai pada taraf diskriptif,yaitu menganalisis dan menyajikan faktasecara sistematik sehingga dapat lebih mudah untuk dipahami dan disimpulkan ,serta dokumentasi dan studi pustaka,Hasil dari penelitian di atas disimpulkan dengan penyelenggaran Tasik Oktober Festival mendongkrak wisatawan untuk berkunjung ke Tasikmalaya dan berdampak positif bagi kegiatan perekonomian Tasikmalaya. Kata kunci : Tasik Oktober Festival (TOF), Industri kreatif